2001
DOI: 10.1182/blood.v97.11.3424
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the INK4a/ARF locus in polycythemia vera

Abstract: The retinoblastoma (Rb), cyclin-dependent kinase (CDK), and CDK inhibitor genes regulate cell generation, and deregulation can produce increased cell growth and tumorigenesis. Polycythemia vera (PV) is a clonal myeloproliferative disease where the mechanism producing increased hematopoiesis is still unknown. To investigate possible defects in cellcycle regulation in PV, the expression of Rb and CDK inhibitor gene messenger RNAs (mRNAs) in highly purified human erythroid colony-forming cells (ECFCs) was screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 46 publications
(40 reference statements)
1
11
1
Order By: Relevance
“…22 Despite claims to the contrary, 23,24 this hypersensitivity does not appear to be the consequence of an abnormality in the negative regulatory hematopoietic phosphatase, SHP-1. 25,26 Indeed, evidence has been obtained for increased activity of a membrane-associated protein tyrosine phosphatase in polycythemia vera erythroid progenitor cells 27 and although overexpression of INK4a and ARF has also been documented in these cells 28 and constitutive phosphorylation of STAT3 has been observed in the granulocytes in a minority of patients, 29 no consistent abnormality of signal transduction or cell cycle regulation has been identified to date in polycythemia vera nor have mutations been identified in p53 or Ras during the chronic phase of the illness. 30 There is evidence for both gain 31,32 and loss 33,34 of suppressor genes in polycythemia vera but exactly which genes and how they might affect erythroid progenitor cell behavior remain unknown.…”
Section: The Pathogenesis Of Polycythemia Vera: Polycythemia Vera Is mentioning
confidence: 99%
“…22 Despite claims to the contrary, 23,24 this hypersensitivity does not appear to be the consequence of an abnormality in the negative regulatory hematopoietic phosphatase, SHP-1. 25,26 Indeed, evidence has been obtained for increased activity of a membrane-associated protein tyrosine phosphatase in polycythemia vera erythroid progenitor cells 27 and although overexpression of INK4a and ARF has also been documented in these cells 28 and constitutive phosphorylation of STAT3 has been observed in the granulocytes in a minority of patients, 29 no consistent abnormality of signal transduction or cell cycle regulation has been identified to date in polycythemia vera nor have mutations been identified in p53 or Ras during the chronic phase of the illness. 30 There is evidence for both gain 31,32 and loss 33,34 of suppressor genes in polycythemia vera but exactly which genes and how they might affect erythroid progenitor cell behavior remain unknown.…”
Section: The Pathogenesis Of Polycythemia Vera: Polycythemia Vera Is mentioning
confidence: 99%
“…42,43 Additional evidence regarding the pathogenetic role of JAK-STAT in MPD includes the demonstration of constitutive activation of STAT3 44 upregulation of negative control elements of the cell cycle (p16/p14), 45,46 and abundance, in erythroid precursors, of anti-apoptotic proteins (e.g., Bcl-x L ). 47,48 The latter molecule is down regulated by AG490-induced inhibition of JAK2. 49 In the last 3 months, six independent studies have reported on the association of an activating mutation JAK2 with the bcr/abl-negative MPD (CPV, ET, MMM, Table1).…”
mentioning
confidence: 99%
“…In a separate study, we recently found that tumor suppressors p16 (INK4a) and p14 (ARF) mRNA levels are enhanced in ECFCs from PV patients. 30 Although none of the studies revealed a mutation in the sequences of the affected proteins, all suggest a possible abnormality in the control of gene expression or modification of key signaling mediators in PV cells. Our current study suggests abnormal regulation of a signaling enzyme at the protein level and thus provides a regulated enzyme as a potential target to treat PV.…”
Section: Discussionmentioning
confidence: 99%